Christian Bioethics in a Post-Christian age - Engelhardt Jr, H. Tristram. (O Mundo da Saúde, 2006)
Christian bioethics conflicts with secular morality and its bioethics. From artificial insemination from donors, embryonic stem-cell research, and abortion to passive euthanasia, the commitments of traditional Christian bioethics collide with those of the dominant secular Western culture. For example, where secular morality cum bioethics regards prenatal diagnosis and selective abortion as integral to responsible parenting, traditional bioethics regards such as a form of murder. The differences are not defined simply in terms of particular prohibitions, but more significantly in terms of the metaphysical force and totalizing moral character of Christian claims. Unlike secular moral philosophy, Christianity provides and demands a definitive orientation in the cosmos. One’s life as a patient, a nurse, and a physician must be metaphysically and morally Christocentric, because the cosmos is Christocentric. On the one hand, for secular bioethics the existence of humans is a surd contingency in a universe that seemingly comes from nowhere, goes to no place, and for no ultimate purpose. On the other hand, Christianity appreciates the dignity of humans as grounded not only in their creation, but in the Incarnation, through which there is the possibility of union with God. Beyond metaphysical differences, there are deep epistemological divergences: traditional Christianity (*) recognizes not just empirical scientific and philosophical knowledge, but also experiential noetic, that is, mystical knowledge of God and reality. Secular and traditional Christian bioethics are thus set within radically different paradigms distinguished not simply by conflicting moral commitments, but by different understandings of the character of knowledge (i.e., epistemology) and the nature of reality (i.e., metaphysics). As a consequence, there is a divergence as to who should be counted as moral experts: moral philosophers versus holy men. This contrast is expressed in the implications of these disagreements for bioethics. In doing so, the Christianity of the first millennium, which continues in Orthodox Christianity, is taken as the primary point of reference, so as better to appreciate the deep historical and conceptual roots of the differences at stake. (*) The term traditional Christianity is admittedly vague and cannot be given much precision within the bounds of this brief article. In this article, traditional Christianity is used to identify: (1) the unbroken Christianity of the first millennium, as well as (2) those Christian groups in the 21st century that are in substantive agreement with its commitments.